Proposta de implementação da metodologia lean manufacturing em uma montadora de veículos - Bostelmann, Marina da Silva (2019)
Lean Manufacturing methodology is applied in industries aiming to improve profitability, market share and customer satisfaction, reducing the problems and consequently increasing quality through statistical tools. This strategy aims to deliver faster and higher quality results to customers, with less waste and as a consequence, operational excellence. The present work, characterized as a case study, has the objective of implementing the Lean Manufacturing methodology applied to the automotive industry, mapping and improving the Upper Level Part Number process applied to the final product axis, thus optimizing the process currently used. As a method, Lean Manufacturing tools were used: laminating and verification sheet, Ishikawa diagram, the five parts, gemba, 5W2H and kaizen. The process was defined, analyzed and measured, thus proposing improvements and applying one of them. However, only one of them was viable economically.